Partial heat acclimation of athletes with spinal cord lesion - Castle, P. C.; Kularatne, B. P.; Brewer, J.; Mauger, A. R.; Austen, R. A.; Tuttle, J. A.; Sculthorpe, N.; Mackenzie, R. W.; Maxwell, N. S.; Webborn, A. D. J. (European Journal of Applied Physiology, 2013)
Heat acclimation (HA) can improve thermoregulatory stability in able-bodied athletes in part by an enhanced sweat response. Athletes with spinal cord lesion are unable to sweat below the lesion and it is unknown if they can HA. Five paralympic shooting athletes with spinal cord lesion completed seven consecutive days HA in hot conditions (33.4 ± 0.6 °C, 64.8 ± 3.7 %rh). Each HA session consisted of 20 min arm crank exercise at 50 % VO2peak followed by 40 min rest, or simulated shooting. Aural temperature (T aur) was recorded throughout. Body mass was assessed before and after each session and a sweat collection swab was fixed to T12 of the spine. Fingertip whole blood was sampled at rest on days 1 and 7 for estimation of the change in plasma volume. Resting T aur declined from 36.3 ± 0.2 °C on day 1 to 36.0 ± 0.2 °C by day 6 (P < 0.05). During the HA sessions mean, T aur declined from 37.2 ± 0.2 °C on day 1, to 36.7 ± 0.3 °C on day 7 (P < 0.05). Plasma volume increased from day 1 by 1.5 ± 0.6 % on day 7 (P < 0.05). No sweat secretion was detected or changes in body mass observed from any participant. Repeated hyperthermia combined with limited evaporative heat loss was sufficient to increase plasma volume, probably by alterations in fluid regulatory hormones. In conclusion, we found that although no sweat response was observed, athletes with spinal cord lesion could partially HA.